The strength and drivers of bird-mediated selection on fruit crop size: a meta-analysis - Palacio, Facundo Xavier (2018)
In seed-dispersal mutualisms, the number of fruit a plant displays is a key trait, as it acts asa signal for seed dispersers that entails fruit removal and exportation of reproductive units(fruit crop size hypothesis). Although this hypothesis has gained general acceptance,forces driving the shape and strength of natural selection exerted by birds on fruit cropsize remains an unresolved matter. Here, we propose that ecological ﬁlters promotinghigh functional equivalence of interacting partners (similar functional roles) translate intosimilar selection pressures on fruit crop size, enhancing selection strength on this trait.We performed a meta-analysis on 50 seed-dispersal systems to test the hypothesisthat frugivorous birds exert positive selection pressure on fruit crop size, and to assesswhether different factors expected to act as ﬁlters (fruit diameter, fruit type, fruiting seasonlength, bird functional groups, and latitude) inﬂuence phenotypic selection regimes onthis trait. Birds promote larger fruit crop sizes as a general pattern in nature. Shortfruiting seasons and a high proportion of species belonging to the same functional groupshowed higher selection strength on fruit crop size. Also, selection strength on fruit cropsize increased for large-fruited species and toward the tropics. Our results support thehypothesis that fruit crop size represents a conspicuous signal advertising the amount ofreward to visually driven interacting partners, and that both plant and bird traits, as wellas environmental factors, drive selection strength on fruit display traits. Furthermore, ourresults suggest that the relationship among forces impinged by phenology and frugivorefunctional roles may be key to understand their evolutionary stability.